Effects of a randomized trial comparing standard and enhanced counseling for men at high risk of prostate cancer as a function of race and monitoring style - Roussi, Pagona (J Health Psychol, 2016)
Despite conflicting guidelines, a significant subset of high-risk men decide to undergo routine prostate cancer screening. Yet, there is a scarcity of available programs, and no studies evaluating interventions to support men in dealing with the psychosocial impact of screening. In this study, one of the first to explore the responses of high-risk men enrolling in a Prostate Cancer Risk Assessment Program (N = 128), patients underwent a prostate cancer risk counseling visit immediately followed by either a cognitive–affective preparation session designed to help them process the information they received or a general health education session. All men in this self-selected sample chose to participate in prostate cancer screening. Men were assessed 3 weeks and 6 months post-counseling. The impact of the enhanced counseling condition on knowledge, perceived risk, expectancies, and intrusive ideation was a function of racial and coping style group. Implications for tailored interventions to maximize preparedness for risk and screening counseling are discussed.